Impact of different levels of zinc and nitrogen on growth, productivity, and quality of aromatic rice cultivated under various irrigation regimes in two districts of Pakistan - Hasnain, Zuhair; Khan, Shahbaz; Nasrullah, Fareeha; Mehmood, Kashf; Ibrar, Danish; Bashir, Saqib; Bakhsh, Ali; Aziz, Irum; Rais, Afroz; Farooq, Naila; Irshad, Sohail; Rashid, Nabila; et al. (Frontiers in Plant Science, 2022)
Rice is a staple food for more than 50% of the global population and it is one of the most valuable cereal crops. To fulfill the dietary requirement of ever-growing world population, an increase in per unit production of rice is direly required. In Pakistan, it stands the 2nd in consumption after wheat, a staple food. A huge gap is observed between yield potential and actual yield of the aromatic rice cultivars at farmer field level. The significant limitations responsible for this gap are shortage of irrigation water, inappropriate application of fertilizers, less plant population, deficiency of micronutrients, improper and poor plant protection measures. Field study was planned to assess the yield response and quality attributes of aromatic rice to three levels of zinc (Zn) and nitrogen (N) under three irrigation regimes (8, 12 and 16 acre inches) in Sheikhupura and Sargodha districts of Pakistan. Irrigation treatments significantly influenced the growth, yield and quality attributes, however, maximum improvement was observed by application of irrigation at 12-acre inches. Among the Zn treatments, application of Zn at 10 kg ha-1 was observed more responsive to improve the growth and quality parameters of aromatic rice crop. In case of N treatments, application of N at 140 kg ha-1 produced the maximum total tillers as well as productive tillers per hill, spikelets per panicle, leaf area index, leaf area duration, crop growth rate, total dry matter, harvest index, kernel length, kernel width and 1000-kernel weight. Application of N at 140 kg ha-1 not only improved the growth attributes but net assimilation rate, photosynthetically active radiation, radiation use efficiency with respect to total dry matter and kernel yield were also increased. The maximum percentage of normal kernels and minimum percentage of opaque, abortive and chalky kernels was also recorded by application of N at 140 kg ha-1. The outcomes of current experiments depicted that application of irrigational water, zinc and nitrogen at 12 acre inches, 10 and 140 kg ha-1 respectively are responsible to achieve maximum resources utilization efficiency along with increased yield and quality of rice.